Pengembangan E-Komik sebagai Media Pembelajaran Materi Dampak Sosial Informarika Kelas X di SMK Negeri 1 Putussibau - Firanda, Yagi; Marlianto, Ferry; Liwayanti , Umi (Indo-MathEdu Intellectuals Journal, 2025)
Flip PDF Professional is a desktop application for creating interactive learning media in flipbook format that can be published on computers, Android, and iOS. This study uses the Research and Development (R&D) methodology. The steps to develop E-Comic-based learning media use the ADDIE model which stands for Analysis, Design, Development, Implementation, Evaluation. This study aims to: (1) Determine the Development of Interactive Learning Media Based on E-Comics in Informatics Subjects for Class X at SMK Negeri 1 Putussibau. (2) Determine the Feasibility of the product on Interactive Learning Media Based on E-Comics in Informatics Subjects for Class X at SMK Negeri 1 Putussibau. (3) Determine the Student Response to Interactive Learning Media Based on E-Comics in Informatics Subjects for Class X at SMK Negeri 1 Putussibau. The results obtained from the media expert test obtained a score of 81% with the category of "very feasible", based on the material expert test obtained a score of 80% with the category of "feasible" for the results of the student response trial of 31 students obtained a result of 85.0% with the category of "very feasible"